1999
DOI: 10.3109/10731199909117685
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Polyethylene Glycol Conjugated Bovine Hemoglobin (PEG-Hb) To Adequately Deliver Oxygen in Both Exchange Transfusion and Top-Loaded Rat Models

Abstract: The purpose of this study was to determine whether a six gram percent (g%) solution of the hemoglobin based oxygen carrier, polyethylene glycol conjugated bovine hemoglobin (PEG-Hb) could adequately deliver oxygen in both partial exchange transfusion and top-loaded rat models. This study measured tissue oxygen tension, circulatory retention and cardiovascular effects following both 30% exchange transfusion and 20 to 25 mL/kg top-loaded infusions of PEG-Hb. Oxygen delivery to rat tissues was determined using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…The direct vasoactive effect of different HBOCs appears to be inversely related to their MW which suggests that small molecules are more vasoconstricting. [15][16][17] Clinical and experimental studies suggest that the order of vasoreactivity is highest for the smaller MW HBOCs including diaspirin cross-linked hemoglobin, moderate for polymerized hemoglobins which contain a portion of small MW hemoglobins, and lowest for surface modified hemoglobins that have higher MWs. 26 The current study supports this hypothesis within a single group of chemically modified HBOCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct vasoactive effect of different HBOCs appears to be inversely related to their MW which suggests that small molecules are more vasoconstricting. [15][16][17] Clinical and experimental studies suggest that the order of vasoreactivity is highest for the smaller MW HBOCs including diaspirin cross-linked hemoglobin, moderate for polymerized hemoglobins which contain a portion of small MW hemoglobins, and lowest for surface modified hemoglobins that have higher MWs. 26 The current study supports this hypothesis within a single group of chemically modified HBOCs.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that small HBOC molecules are more vasoconstricting. [15][16][17] Presumably, pronounced vasoconstriction would be disadvantageous because it could limit optimal delivery of oxygen to tissues.…”
Section: Méthode : Des Rats Anesthésiés à L'isoflurane (N = 6-7 Par Gmentioning
confidence: 99%
“…The Bohr effect has also been shown to be more pronounced in bovine Hb, which allows an even better O 2 delivery at lower pH values. It has also been shown that this blood substitute does not change hemodynamics with respect to PCO 2 and pH (1,6,12,17,19,23). HBOC-201 is modified by cross-linking of the ␣,␤-dimers to form a tetrameric structure that does not dissociate as rapidly as free Hb (14).…”
mentioning
confidence: 96%
“…Additionally, the primary structures of these substances are very similar [15]. The synthesised blood additive exhibits a p50 value of 16 mm Hg and a cooperativity of 2.1, which, according to Conover et al [6], results in optimised conditions for oxygen release. An effective concentration of the carrier of approximately 3 g/dl in blood plasma is reasonable.…”
Section: Characteristics Of the Blood Additive -Actual Drug Developmentsmentioning
confidence: 99%
“…A further very important property is an optimal oxygen affinity, which is not even found in normal blood which exhibits a half-saturation pressure (p50) of approximately 25 mm Hg. Investigations carried out by Conover et al [6] showed that the provision of oxygen to organs by means of plasmatic oxygen carriers occurs best when these agents exhibit a half-saturation pressure of between 15 und 20 mm Hg. The oxygen-transporting blood additive should be able to compensate for a poor tissue oxygenation whereby it is probable that the haemoglobin saturation will need to fall below 50%, as suggested by measurements of tissue oxygen partial pressure below 25 mm Hg (already in normal tissue, see e.g.…”
Section: The Authors' Concept Of a Blood Additivementioning
confidence: 99%